IMPROVEMENT OF COST ACCOUNTING AT LIGHT INDUSTRY ENTERPRISES BASED ON INTERNATIONAL STANDARDS - Sadikov Zafarbek, Adilbekovich (THE INNOVATION ECONOMY, 2025)
this article thoroughly analyzes theoretical and practical aspects of improving the cost accounting system in light industry enterprises based on International Financial Reporting Standards (IFRS). The research demonstrates that implementing international standards significantly enhances cost accuracy, calculation speed, and the effectiveness of managerial decisions. Empirical analysis indicated considerable reductions in production costs among enterprises that adopted international standards.